DevOps-Powered Continuous Testing: Driving Efficiency in Property and Casualty Cloud Migration - Gollapudi, Pavan Kumar; Subbian, Rajkumar Govindaswamy (Science and Technology: Developments and Applications Vol. 7, 2025)
Background: Shifting to the cloud comes with security threats and systems performance glitches or integrating legacy applications with brand-spanning new cloud infrastructures are the predicaments they need to engage in. Continuous testing as DevOps emerged as a remedy against the problems to make for smooth and successful cloud migration. Aim: The study examines Continuous Testing (CT) in a DevOps environment for cloud migration within the Property & Casualty (P&C) insurance industry and InsurTech companies. The study evaluates the impact of AI/ML-driven test automation, security testing, and performance validation using tools like Selenium, JUnit, and TestNG; CI/CD pipelines such as Jenkins, GitHub Actions, and Azure DevOps. Methodology: This study takes a mixed methods approach that incorporates case studies, industry surveys, and experimental testing to assess the efficiency of Continuous Testing in cloud migration strategies. Through experimentation with automated testing tools such as Selenium, JUnit, and Jenkins, the improvements in efficiency were measured. A comparative analysis was employed to measure the performance indicators prior to and after the CT implementation. Findings: Continuous testing (CT) substantially enhances cloud-migration efficiency for P&C insurance. Companies that have had CT in their version of DevOps have executed a 40-60% increase in software release cycles, leading to faster deployments. Automated testing dragged post-deployment issues down by 35%, thereby increasing the reliability of the software. Compliance with industry requirements was much better because continuous security checks lessen risks. Another benefit included a reduction of about 20-30% in testing costs due to automation that replaced human testing. On top of this, the way for more applications to be resilient to system failures was opened; applications were supported and maintained. The post-migration data should always specify that applications have 99.9% uptime. In the heavily regulated insurance sector, continuous testing thus becomes a much faster, more secure, and cost-effective measure for moving to the cloud. Conclusion: The adoption of continuous testing into DevOps for migration to the cloud disrupted the status quo in many sectors, especially in property & casualty insurance, banking, entertainment, and aviation.